Industrialisation and society : a social history, 1830-1951 - Hopkins, Eric. (London ; New York : Routledge, 2000)
An essential introduction to the effects of industrialisation on British society, from Queen Victoria's reign to the birth of the Welfare State in the 1940s. It includes sections on the Victorian inheritance and the two world wars.
Book Cover; Title; Contents; Tables; Introduction; The Victorian inheritance; The mid-century years; After equipoise: urban problems, 1870 1900; Industrial change and the countryside, 1830 1951; The challenge from the left; Edwardian England and the Liberal reforms; The Great War, 1914 18; The inter-war years, 1918 39; War and the coming of the Welfare State; Envoi; Notes; Select bibliography; Index.
Includes bibliographical references (pages 280-291) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Industrialization -- Social aspects -- Great Britain -- History; Great Britain -- Economic conditions -- 19th century; Great Britain -- Economic conditions -- 20th century; Great Britain -- Social conditions -- 19th century; Great Britain -- Social conditions -- 20th century; Industries -- Social aspects -- Great Britain -- History; Industrialisation -- Aspect social -- Grande-Bretagne -- Histoire; Grande-Bretagne -- Conditions économiques -- 19e siècle.; Grande-Bretagne -- Conditions économiques -- 20e siècle.; Grande-Bretagne -- Conditions sociales -- 19e siècle.; Grande-Bretagne -- Conditions sociales -- 20e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Economic history; Industrialization -- Social aspects; Industries -- Social aspects; Social conditions; Great Britain; Industrialisierung; Großbritannien; Industrialisatie; Sociale geschiedenis; 1800-1999; History